The reproducibility and clinical utility of the 3D camera for measuring scar height, with a protocol for administration. Issue 4 (7th March 2017) - Tyack, Z.; Simons, M.; Kimble, R. M.; Muller, M. J.; Leung, K.
Abstract : Background: This study aimed to determine the reproducibility and clinical utility of a 3D camera for measuring burn scar height in adults. Methods: Participants from a larger prospective longitudinal study were included. Reproducibility data were collected using an immediate test‐retest interval and a 1‐2 week test‐retest interval and included reliability and agreement. The LifeViz ™ 3D camera was used to measure scar height. Reproducibility was tested using the Intraclass Correlation Coefficient (ICC), percentage agreement within 1 mm between test and retest, standard error of measurement, smallest detectable change (SDC) and Bland Altman limits of agreement. Results: Burn scar images from 55 adult participants were included. Intra‐rater reliability was acceptable using an immediate retest interval (maximum and minimum height ICC=0.85, 0.86 respectively). Agreement using an immediate retest interval was borderline acceptable (maximum and minimum height SDC=1.11, 0.69 respectively) to detect changes of close to 1 mm. Reproducibility was largely not acceptable using a 1‐2 week test‐retest interval (eg, maximum and minimum height ICC=0.34, 0.68 respectively; maximum and minimum height SDC=2.66, 1.16). The clinical utility of the camera was supported for scars over relatively flat areas and well‐defined border margins. A protocol for administration of the camera was developed. Conclusion: The 3D camera appears capable of detecting gross changes or differences in scar height above the normal skin surface, in adults with scars over relatively flat areas and well‐defined border margins. However, further testing of reproducibility using a shorter test‐retest interval than 1‐2 week retest is recommended to confirm the suitability of the device for measuring changes or differences in scar height.